DESIGN OF 5 STORIES REINFORCED CONCRETE STRUCTURE DATA CENTER BUILDING IN SOUTH PONTIANAK SUB-DISTRIC: PERANCANGAN STRUKTUR BETON BERTULANG 5 LANTAI PADA BANGUNAN GEDUNG DATA CENTER DI KECAMATAN PONTIANAK SELATAN - Kurniawan, Farhan; Purnama, Ikhwan Arief; GINTING, RAFANI; Irpan, Muhammad (RETENSI, 2023)
The demand for supporting facilities in the advancement of information technology, specifically in Pontianak City, is increasing, a building that is suitable, strong, and earthquake resistant is needed as an effort to support the sustainability of centralized information technology infrastructure. The design of the data center also used a hebel brick as a wall to reduce the dead load of the building. The entire structure uses reinforced concrete structures in soft soil conditions (SE) with a intermediate moment frame system (IMF) that refers to SNI 2847-2019, also takes into the calculation of seismic aspects according to SNI 1726-2019 with the spectrum response method. The serviceability of this building is estimated according to the service load of office buildings and computer rooms based on SNI 1727-2020. This 5-storey building is modeled and structural analysis using the SAP2000 program, as well to 2D detail engineering design using the AutoCAD 2020 program, has a site area of 980 m². The strength of the foundation structure is based on Cone Penetration Test on Purnama street. All structural components use concrete strength fc' 30 MPa and steel strength 400 MPa. The design results thick deck plate 150 mm and floor/stair/step plate 120 mm, prymary beam and sloof B1 with dimensions 300×600 mm, secondary beam B2 with dimensions 250×500mm, secondary beam B3 with dimensions 150×300mm, primary column K1 with dimensions 600×600 mm, column K2 with dimensions 350×350mm, fondation pilecap P1 with dimensions 3100×3100×700mm, fondation pilecap P2 with dimensions 5100×1800×700mm, fondation pilecap P3 with dimensions 700×700×500mm with bearing capacity of square pile dimensions 350×350mm with length of 24m. Keywords: Building, Data center, Structure, Reinforced concrete, IMF